Comparative assessment between the defined dental age of tooth determined by the Cameriere method, and the calendar age of 6–7 years old children of the Carpathian region of Ukraine - Макєєв, Валентин Федорович; Ісакова, Ольга Олексіївна (Actual Dentistry, 2019)
Purpose. To evaluate the chronological and dental age of children in Lviv and the Lviv region aged 6–7 years with the help of the modified formula Cameriere. Methods. Оrthopantomograms 23 children (16 boys and 7 girls) aged 6–7 years from Lviv and Lviv region have been used for this study. A questionnaire was developed for the submission of individual patient data and a standardized format for making their indicators derived from orthopantomograms (OPG). The examination of the area of the lower seven teeth on the left was done using the Cameriere method and the age of the child was evaluated, which was further compared with the chronological age. Results. The obtained results of the study showed a high accuracy and reliability of the estimation of dental age in children up to 6–7 years with the help of the Cameriere formula modified by us. The research is based on the detection of physiological changes (the rate of formation of the roots) in the permanent teeth of children using the X-ray method. Evaluating the results obtained by two methods, among girls and boys of the selected age group, a statistically significant strong correlation between the chronological age and the age calculated by the Cameriere method was revealed. Conclusions. The results of the studies have shown the suitability of the Cameriere formula modified during the process, based on the assessment of open tops and the number of teeth with completed root formation as a marker for the physiological development of the child and one that can be used to determine the child’s age. Key words: dental age, regression formula Cameriere, panoramic radiograph, аge estimation; teeth; orthodontics, the Cameriere method.